Clinical Significance and Outcome in Patients with Asymptomatic Versus Symptomatic Subsegmental Pulmonary Embolism - Rodríguez-Cobo, Ana; Fernández-Capitán, Carmen; Tung-Chen, Yale; Salgueiro-Origlia, Giorgina; Ballaz, Aitor; Bortoluzzi, Cristiano; Sarlon-Bartoli, Gabrielle; Pesce, Maria Lourdes; Najib, Dally; Monreal, Manuel; The Riete Investigators; Bosevski, Marijan; et al. (MDPI AG, 2023)
The clinical significance and optimal therapy of patients with subsegmental pulmonary embolism (SSPE) remain controversial. We used the data in the RIETE Registry to compare the baseline characteristics, treatment, and outcomes during anticoagulation and after its discontinuation in patients with asymptomatic vs. symptomatic SSPE. From January 2009 to September 2022, there were 2135 patients with a first episode of SSPE, of whom 160 (7.5%) were asymptomatic. Most patients in both subgroups received anticoagulant therapy (97% vs. 99.4%, respectively). During anticoagulation, 14 patients developed symptomatic pulmonary embolism (PE) recurrences, 28 lower-limb deep vein thrombosis (DVT), 54 bled, and 242 died. The patients with asymptomatic SSPE had similar rates of symptomatic PE recurrences (hazard ratio (HR): 2.46; 95% CI: 0.37-9.74), DVT (HR: 0.53; 95% CI: 0.03-2.80), or major bleeding (HR: 0.85; 95% CI: 0.21-2.42) to those with symptomatic SSPE, but had a higher mortality rate (HR: 1.59; 95% CI: 1.25-2.94). The rate of major bleeding outweighed the rate of PE recurrences (54 major bleeds vs. 14 PE recurrences), and the rate of fatal bleeds outweighed the rate of fatal PE recurrences (12 vs. 6 deaths). After discontinuing anticoagulation, the patients with asymptomatic SSPE had a similar rate of PE recurrences (HR: 1.27; 95% CI: 0.20-4.55) and a non-significantly higher mortality rate (HR: 2.06; 95% CI: 0.92-4.10). The patients with asymptomatic SSPE had similar rates of PE recurrences to those with symptomatic SSPE, during and after discontinuing anticoagulation. The unexpectedly higher rate of major bleeding than recurrences highlights the need for randomized trials to find the best management.